The effect of Bifidobacterium animalis lactis HNO19 supplementation among pregnant and lactating women on interleukin-8 level in breast milk and infant's gut mucosal integrity (Medical Journal of Indonesia, 2017)
Background: Newborn's gut mucosal is not fully developed, therefore infants are prone to diarrhea. Probiotic supplementation is known to induce the gut mucosal maturity. This study aimed to identify whether probiotics supplementation among pregnant women since the third trimester would increase the infant's gut mucosal integrity. Methods: A double-blind, randomized clinical trial was conducted to understand the potential effect of probiotic supplementation on the level of probiotics and IL-8 in breastmilk, urine IFABP, faecal α-1-antytripsin (AAT) and calprotectin in infant's at birth (V0) and three-months old (V3). A single strain of Bifidobacterium lactis animalis HNO19 (known as DR10) was used since it was not the resident bacteria. The study was held at Budi Kemuliaan Hospital and its satellite clinics from December 2014 to December 2015. Results: About 14% (5/35) and 20% (7/35) of the subjects had DR10 in the breastmilk's colostrum and at the age of 3-months. The median values of IL-8 in the probiotic group vs the placebo group at V0 and V3 were 2810,1 pg/mL vs 1516.4 pg/mL (p=0.327) and 173.2 pg/mL vs 132.7 pg/mL (p=0.211) respectively. IFABP level 211.7 ng/mL vs 842.5 ng/mL (p=0.243) and 25.3 ng/mL vs 25.1 ng/mL (p=0.466); AAT 136.2 mg/dL vs 148.1 mg/dL (p=0.466) and 24 mg/mL vs 29.72 mg/mL (p=0.545); Calprotectin 746.8 ng/mL vs 4645.2 ng/mL (p=0.233) and 378.6 ng/mL vs 391.3 ng/mL (p=0.888). Conclusion: Probiotic DR10 given to pregnant women since the 3rd trimester can be found in colostrum and 3-months breastmilk. However, it did not affect the level of other probiotics or IL-8 and the gut mucosal integrity.